(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper we present about performance appraisalsystems with special emphasis on case studies of private companies. Employeesare performing well when they are productive. Productivity implies both concernfor effectiveness and efficiency, effectiveness refers to goal accomplishment.However it does not speak of the costs incurred in reaching the goal. That iswhere efficiency comes in. Efficiency evaluates the ratio of inputs consumed tooutputs achieved. It is not desirable to have objective measures ofproductivity such as hard data on effectiveness, number of units produced, orpercent of crimes solved etc and hard data on efficiency.